2009
DOI: 10.5713/ajas.2009.80301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Vegetable Oils on Growth and Fatty Acid Profile of Rohu (Labeo rohita, Hamilton); Evaluation of a Return Fish Oil Diet to Restore Human Cardio-protective Fatty Acids

Abstract: Two experiments in the sequential order were conducted to determine the effects of different dietary lipid sources on the growth and fatty acid composition of rohu (Labeo rohita) and to examine the viability of a return fish oil finisher diet in restoring the human cardio-protective fatty acid profile. In the first experiment, fish were fed either with coconut oil (D1), olive oil (D2), sunflower oil (D3), linseed oil (D4) and fish oil (D5) as the main lipid source in the isonitrogenous diet for 90 days. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…This suggested that SO, CO, PeO, and PaO could be considered potential oils for replacement of FO in diets for blunt snout bream fingerlings. These results were in accordance with a number of previous studies of several freshwater species including white sturgeon, Acipenser transmontanus (Xu et al ), Murray cod, Maccullochella peelii peelii (Francis et al ), and Rohu, Labeo rohita (Karanth et al ). Although no significant differences in growth performance of fish among different experimental groups were found in this study, we thought significant differences in BWG and FCR among the different groups might be observed if this trial could be continued for a longer time.…”
Section: Discussionsupporting
confidence: 93%
“…This suggested that SO, CO, PeO, and PaO could be considered potential oils for replacement of FO in diets for blunt snout bream fingerlings. These results were in accordance with a number of previous studies of several freshwater species including white sturgeon, Acipenser transmontanus (Xu et al ), Murray cod, Maccullochella peelii peelii (Francis et al ), and Rohu, Labeo rohita (Karanth et al ). Although no significant differences in growth performance of fish among different experimental groups were found in this study, we thought significant differences in BWG and FCR among the different groups might be observed if this trial could be continued for a longer time.…”
Section: Discussionsupporting
confidence: 93%
“…Considered in terms of survival and growth, LO, SO, CO, RO and BT could be considered potential replacement oils for dietary FO. Similar results have been reported for other freshwater fish species including the rohu, Labeo rohita (Karanth, Sharma, Pal, & Venkateshwarlu, ), beluga sturgeon, Huso huso (Hosseini & Kenari, ), and largemouth bass, Micropterus salmoides (Subhadra et al., ) with no significant differences observed in growth between different lipid sources. Li et al.…”
Section: Discussionsupporting
confidence: 86%
“…In rohu an increased level of accumulation of EPA and arachidonic acid (20:4n6) over their respective initial level in liver and muscle at 21°C and 32°C suggested bio-transformation of the parent FAs of these series (Samantaray and Mishra, 2004). Karanth et al (2009) reported high deposition of linolenic acid (18:3n3) and EPA in rohu liver feeding with high linolenic acid diet. In the present study on rohu, the dietary 18:3n3 of control and algal diets could induce higher liver EPA level.…”
Section: Fattymentioning
confidence: 99%
“…The FA of rohu and other freshwater fishes were studied by several authors (Ackman et al, 2002;Prabhakara Rao et al, 2010, Jakhar et al, 2012. Changes in growth performance and FA profile of rohu were reported due to the effect of different vegetable oils (Karanth et al, 2009) and due to the different levels of dietary n-3 (Chittem and Kunda, 2013). In both these studies rohu FA profile is found to be affected by the diet.…”
Section: Mishra Et Al 11(3): 005-016 (2017)mentioning
confidence: 99%